2003
DOI: 10.1111/j.1651-2227.2003.tb00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Orlistat treatment in obese prepubertal children: a pilot study

Abstract: Aim: This study investigated orlistat treatment in obese prepubertal children with regard to tolerance, safety and psychological well‐being. Methods: 11 healthy, severely obese prepubertal children (age 8.3–12.3 y, body mass index standard deviation score 5.3–9.2) were recruited for a 12wk open treatment. Before, during and after treatment, the participants were investigated by psychological evaluation, blood chemistry, and parameters reflecting obesity and fat mass. Results: The participants were able to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 8 publications
2
26
1
1
Order By: Relevance
“…While no weight loss medications have been approved by the FDA for use in children under the age of 16 203 , several studies employing medications efficacious in overweight adults have also shown promise for use in adolescents. The research examining the impact of medication on weight loss in overweight children is minimal 208 .…”
Section: Medical Treatments For Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…While no weight loss medications have been approved by the FDA for use in children under the age of 16 203 , several studies employing medications efficacious in overweight adults have also shown promise for use in adolescents. The research examining the impact of medication on weight loss in overweight children is minimal 208 .…”
Section: Medical Treatments For Obesitymentioning
confidence: 99%
“…Several studies support the use of orlistat to significant reduce weight in overweight children (Norgren et al, 2003) and adolescents [223][224][225] , though one study of 40 overweight adolescents found no difference between teens receiving orlistat and those receiving placebo 226 . Unfortunately, these studies only examined outcomes as far out as 6 months.…”
Section: Medical Treatments For Obesitymentioning
confidence: 99%
“…The National Childhood Obesity Center, Stockholm, is a referral center for children with severe obesity, the aim of which is to evaluate obesity treatment [13,14,15]. All children and their parents have agreed to continuous treatment for 5 years.…”
Section: Methodsmentioning
confidence: 99%
“…The nonsystemic mechanism rendered it a good choice for investigation in the pediatric population where long-term safety is a concern. Small pilot studies published the feasibility and tolerability of orlistat in adolescents [11][12][13][14]. In 2003, orlistat was approved by the FDA for the management of obesity in individuals age 12 to 16 years (www.fda.gov/foi/esum/2003/20766se5-018_Orlistat_BP CA_CLINICAL_ltr.pdf).…”
Section: Orlistatmentioning
confidence: 99%